Implementasi Kebijakan Gereja Masehi Injili di Timor (GMIT) Tentang Jabatan Pengajar Periodik dalam Jemaat - Daud Saleh Luji (UKI Press, 2022)
In 2010 GMIT established a GMIT Constitution which regulates the teaching position as a periodic office chosen by the congregation (article 30:2-3). From the basic GMIT system, it encountered various problems in its implementation. To find out the problems in the background above, the focus of this research is how to implement the GMIT Basic Rules regarding teaching positions (presbyters) in GMIT congregations. This study uses a qualitative approach with 64 informants spread over 7 kalsis of GMIT area with observation, interview and documentation study techniques. The results obtained from this study are that the policy regarding teaching positions in the congregation as stated in the 2010 Church Order has not been implemented properly because: most of the congregations at GMIT do not yet have teachers; there are also congregations that have not implemented this policy because they want a professional teacher, appointed and financed by the congregation as a church employee with a church council decree; there is a small number of congregations at GMIT that already have teachers but most of them are lay people who give themselves to serve; because the 2010 Church Order provides space for the church to choose a teacher who may not have a PAK or Theological Education background, those who are elected should be trained by the church regularly for several months. However, the reality in the field is that the training before ordination only lasted 3 days and even then, more and more joined the provision of elders and deacons.